Open data and right to information in Malaysia: a comparative analysis - Daud, Mahyuddin; Zulhuda, Sonny (Institute of Electrical and Electronics Engineers Inc., 2019)
The right to freedom of information is no longer new. As early as 1960s, countries around the world have started to recognise people’s right to know information that governments withhold. Under this pretext, the public has the right to know information they ought to know because they directly affect their lives. However, it is also recognised that certain information needs to be classified as secret for national security and other specified reasons. In light of the above, the US Freedom of Information Act 1966, the UK Freedom of Information Act 2000 and were seen as regulatory models that could act as reference for the Malaysian legislative framework. These jurisdictions and some others have long recognised freedom of information as basic constitutional right. In 2011, there were attempts by the Malaysian state governments i.e. Penang and Selangor to introduce Freedom of Information Enactments. However, such efforts have yet to be implemented at the Federal level due to lack of constitutional clarity on the existence of such right. In the era of digitalisation and open data, governments have moved from the tradition of keeping information secret to being transparent in line with the 4 th Industrial revolution. This paper seeks to record the development of freedom of information and data openness in Malaysia. The authors submit that it is timely for the FOI laws to be integrated at the federal level to ensure Malaysian readiness to face the challenges of the upcoming 4 th Industrial revolution.